Ablation of low-molecular-weight FGF2 isoform accelerates murine osteoarthritis while loss of high-molecular-weight FGF2 isoforms offers protection - Burt, Patience Meo (J Cell Physiol, 2018)
FGF2 is an essential growth factor implicated in osteoarthritis (OA), and deletion of full-length FGF2 (Fgf2(ALLKO)) leads to murine OA. However, the FGF2 gene encodes both high-molecular-weight (HMW) and low-molecular-weight (LMW) isoforms, and the effects of selectively ablating individual isoforms, as opposed to total FGF2, has not been investigated in the context of OA. We undertook this study to examine whether mice lacking HMW FGF2 (Fgf2(HMWKO)) or LMW FGF2 (Fgf2(LMWKO)) develop OA and to further characterize the observed OA phenotype in Fgf2(ALLKO) mice. Fgf2(HMWKO) mice never developed OA, but 6- and 9-month-old Fgf2(LMWKO) and Fgf2(ALLKO) mice displayed signs of OA, including eroded articular cartilage, altered subchondral bone and trabecular architecture, and increased OA marker enzyme levels. Even with mechanical induction of OA, Fgf2(HMWKO) mice were protected against OA, while Fgf2(LMWKO) and Fgf2(ALLKO) displayed OA-like changes of the subchondral bone. Before exhibiting OA symptoms, Fgf2(LMWKO) or Fgf2(ALLKO) joints displayed differential expression of genes encoding key regulatory proteins, including IL-1β, insulin-like growth factor 1, bone morphogenetic protein 4, hypoxia-inducible factor 1, B-cell lymphoma 2, Bcl2- associated X protein, a disintegrin and metalloproteinase with thrombospondin motifs 5, ETS domain–containing protein, and sex-determining region Y box 9. Moreover, Fgf2(LMWKO) OA cartilage exhibited increased FGF2, FGF23, and FGFR1 expression, while Fgf2(HMWKO) cartilage had increased levels of FGFR3, which promotes anabolism in cartilage. These results demonstrate that loss of LMW FGF2 results in catabolic activity in joint cartilage, whereas absence of HMW FGF2 with only the presence of LMW FGF2 offers protection from OA.